Jarosława Iwaszkiewicza wiersz „pośmiertny” - Brzozowski, Jacek (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The main subject of the text is the poem with an incipit of “Mamo, czy ja oślepłem…” (“Mother, have I gone blind…”), which is the final poem in the Pini di Roma series, published in the second edition of Śpiewnik włoski from 1978. The interpretation of the poem is preceded by remarks on the content and composition of the two editions of the volume (the first one dated 1974, and the second one) as well as a number of remarks placing the poem in the context of European and Polish literary and cultural tradition. The poetics of “Mamo, czy ja oślepłem…” — the conversation of the dying poet with his deceased mother — allows the text to be perceived as a peculiar ‘posthumous’ poem. At the same time, the poem is very elevating, optimistic and gives a great amount of hope in comparison to other death-themed lyrics by the author of Muzyka wieczorem.